A highly sensitive thrombin generation assay for assessment of recombinant activated factor VII therapy in haemophilia patients with an inhibitor - Livnat, Tami; Martinowitz, Uri; Zivelin, Ariella; Rima, Dardik; Kenet, Gili (Thrombosis and Haemostasis, 2011)
Bypass agents are the common treatment for haemophilia patients who develop inhibitory antibodies. Laboratory assessment of the efficacy of bypassing agent therapy is a challenge. In the present work we modified the conditions triggering thrombin generation (TG) assay in order to find the most sensitive assay for detection of rFVIIa and its analogue NN1731 in haemophilic plasma. TG was measured in samples of normal plasma, plasma of haemophilia patient with inhibitors, as well as haemophilia induced plasma. Recalcification-induced TG was compared to tissue factor (TF) -induced TG in the presence and absence of rFVIIa and NN1731. Recalcification-induced TG (without TF) in haemophilic plasma yielded baseline flat curves, with increased TG as a consequence of spiking the plasma rFVIIa. Using our system, we observed both dose-dependence and time-dependence of rFVIIa effect on TG. Elevated concentrations of TF mask the difference between rFVIIa-treated and non-treated haemophilic plasma. NN1731 yielded normal-isation of recalcification-induced TG curves (without TF) which may reflect high potency. In conclusion, we suggest that triggering TG by recalcification-only may be the most sensitive assay for determining the impact of bypassing agents in haemophilic plasma, and may serve as a caution surrogate safety marker in future studies.
Keywords: Haemophilia therapy; factor VIII inhibitors; coagulation factors; haemophilia A / B